Chat GPT as A Learning Assistant for Islamic Education: A Study In Madrasah Ibtidaiyah - Hasan, Moh ferdi; Patty, Akbar; Sani, Akbar; Taufiq, Firmanda (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2023)
The artificial technology revolution has penetrated various sectors including intelligence education, but its implementation in basic Islamic education remains limited and has not been comprehensively explored. This gap creates an urgency to examine the potential of ChatGPT artificial intelligence as a learning assistant in the context of Islamic education at the elementary level. This research aims to analyze the effectiveness of ChatGPT integration in improving understanding of Islamic concepts among Madrasah Ibtidaiyah (Islamic Elementary School) students. Using a mixed method approach with sequential explanatory design, this research involved 80 students from grades IV-VI from two Madrasah Ibtidaiyahs in Jember and 12 teachers and administrators. The experimental group received ChatGPT-assisted learning developed for basic Aqidah Akhlak (Islamic Creed and Ethics) and Fiqh (Islamic Jurisprudence) materials, while the control group followed conventional methods. The results showed a significant improvement in conceptual understanding in the experimental group (Cohen's d = 1.38) compared to the control group. Qualitative analysis revealed important findings about the transformation of the teacher's role, the technology adaptation process, and AI integration models based on Islamic pedagogical principles such as tawazun (balance), tabayyun (verification), uswah (exemplary), and ta'awun (collaboration). The research results also showed that ChatGPT's effectiveness varied based on the type of material, with procedural materials such as Fiqh benefiting more compared to abstract conceptual materials such as Aqidah. This research contributes to the development of an integrative model of ChatGPT usage in Islamic education that enriches the learning experience while maintaining traditional values.